A new transfer entropy method for measuring directed connectivity from complex-valued fMRI data - Li, Wei-Xing; Lin, Qiu-Hua; Zhang, Chao-Ying; Han, Yue; Calhoun, Vince D. (Frontiers in Neuroscience, 2024)
Background: Inferring directional connectivity of brain regions from functional magnetic resonance imaging (fMRI) data has been shown to provide additional insights into predicting mental disorders such as schizophrenia. However, existing research has focused on the magnitude data from complex-valued fMRI data without considering the informative phase data, thus ignoring potentially important information.We propose a new complex-valued transfer entropy (CTE) method to measure causal links among brain regions in complex-valued fMRI data. We use the transfer entropy to model a general nonlinear magnitude-magnitude and phasephase directed connectivity, and utilize partial transfer entropy to measure the complementary phase and magnitude effects on magnitude-phase and phase-magnitude causality. We also define the significance of the causality based on statistical test and shuffling strategy of the two complex-valued signals.Results: Simulated results verified higher accuracy of CTE compared to four causal analysis methods, including a simplified complex-valued approach, and three real-valued approaches. Using experimental fMRI data from schizophrenia and controls, CTE yields results consistent with previous findings but with more significant group differences. The proposed method detects new directed connectivity related to the right frontal parietal regions, and achieves 10.2% ~ 20.9% higher SVM classification accuracy when inferring directed connectivity using anatomical automatic labeling (AAL) regions as features.The proposed CTE provides a new general method for fully detecting highly predictive directed connectivity from complex-valued fMRI data, with magnitudeonly fMRI data as a specific case.